The Role of The Spotlight Initiative in Overcoming Femicide in Mexico - Pridiyastuti, Herti; Anggraini, Yayuk; Alexandra, Frisca; Purnawarman, Andi (Pusat Studi Gender Universitas Jember, 2024)
Gender-based violence (GBV) is an issue that has received attention at the international level. In Mexico, almost 50% of women have reported being victims of violence perpetrated by their partner or ex-partner to the point of their death. The type of GBV that has experienced a significant increase is femicide or the killing of women just because of gender. The number of cases of femicide in Mexico has averaged 1.500 cases annually since 1985. In the period 1993-2005, there were at least 370 victims femicide that have been identified. This causes Mexico to become a country that is considered unsafe for women, especially with a high level of impunity in Mexico, where 93% of crimes are not reported nor investigated, including femicide. The machismo culture that is very attached to social life in Mexico emphasizes how domination is owned by men over women. The Spotlight Initiative program in Mexico is one of the government's efforts aimed at strengthening, complementing, and supporting existing gender-related initiatives in Mexico, particularly for femicide and violence against women. With 2 phases, the first phase in 2019-2021 and the second phase in 2021-2022, the Spotlight Initiative program is expected to have a positive impact on women in Mexico and can also eliminate acts of violence against women in various forms. However, the program has no significant effect on the level of femicide that occurs in Mexico. The strong influence of machismo culture has become a strong factor in its occurrence femicide in Mexico.